Mexico : 2021 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
Spurred by strong U.S. growth and rising vaccination rates, the economy is rebounding. The government has successfully maintained external, financial, and fiscal stability despite the deepest recession in decades. Nonetheless, Mexico is bearing a very heavy humanitarian, social, and economic cost from COVID-19, including over half a million excess deaths, sizable under-employment, an increase in already-high levels of poverty, and learning losses for the young. Real income per capita is continuing its long-run divergence from the U.S., while additional challenges are emerging from technological shifts and climate change.